IMPLEMENTATION OF IoT-BASED SMART PARKING USING RFID - Anggraini, Nisa; Dwiyanti, Siti Maryam; Putri, Tasya Amalia; Sari, Yandha Pradita; Lusambudi, Anggi Christian; Wahyu, Ari Purno (CENTRAL ASIA AND THE CAUCASUS, 2022)
The parking area is urgently needed in public places such as malls and so on. As time goes by, the development of the productivity of a car in Indonesia evolving so rapidly so that an empty parking lot will also be more and more hard to find. The drivers will be hard to find a parking space so that it will keep spinning to looking for the empty parking spaces, it certainly will make the drivers confusion about which makes the drivers does not park their car. Even lately, the case of car theft in parking lots has increased greatly due to security systems and data that have not been properly managed. The parking area usually using conventional tickets that are easily lost and fell from a pocket that can be stolen by thieves and thieves will take the stolen car from the parking lot and escape using that ticket. This problem can be solved by smart parking system. Smart parking system is a system that can facilitate drivers looking for parking and parking transactions. In this research the researcher will using ethernet shield for sending the data from system to web or vice versa. The aim of his research is to build a smart parking system from transaction and monitoring of parking slots that can be seen on the website. The system consists of a microcontroller, using MFRC522 for transactions, using ultrasonic to detect parking slots, ethernet shield to send the data to database for display parking slot data on website and from database sent to LCD for display user data.